INTEGRASI NILAI BELA NEGARA KEPADA GENERASI MUDA UNTUK PENGUATAN KARAKTER BANGSA TENTANG PERJUANGAN KEMERDEKAAN INDONESIA PADA TAHUN 1945 –1949 DI SUMATERA TIMUR - Satria Chandra (Jurnal Pendidikan Sejarah Humaniora dan Ilmu Sosial, 2026)
This study examines the role of integrating national defense values ​​among the younger generation in strengthening national character, particularly through an understanding of Indonesia's struggle for independence (1945-1949) in East Sumatra. The research background is based on the phenomenon of weak historical and patriotic awareness among adolescents, which has the potential to reduce social cohesion and commitment to national unity. The main objectives of the study are: (1) to identify the level of knowledge and attitudes of the younger generation towards the struggle for independence in East Sumatra, (2) to evaluate the effectiveness of national defense-based education programs in increasing historical awareness, and (3) to formulate an integrative strategy that can be adopted by educational institutions and the community. The results of the study indicate that only 34.7% of respondents have adequate knowledge about the struggle for independence in East Sumatra, while 41.2% demonstrate low patriotic attitudes. Participation in the national defense program was shown to have a significant positive effect on increasing knowledge (β=0.31, p<0.01) and patriotic attitudes (β=0.27, p<0.01). The regression model explained 48% of the variance in changes in patriotic attitudes (R²=0.48). Additional qualitative analysis through in-depth interviews revealed that the main inhibiting factors were the lack of a local history-based curriculum and inadequate supporting facilities.